Efforts to Improve Teacher Well Being Through a Positive Psychology Approach: a Systematic Literature Review - Dasep Saepullah; Zarina Akbar (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
This study is a systematic review that aims to identify, analyze, and synthesize recent findings related to positive psychology interventions in improving teacher well-being. The review highlights that teacher well-being is a central issue in global education, affected by work pressures, policy changes and lack of organizational support. Through an analysis of 14 international journals indexed in the last five years, it was found that positive psychology interventions such as mindfulness training, gratitude, character strengthening, and organizational support consistently improved aspects of teacher well-being, including positive emotions, resilience, self-efficacy, dedication, and job satisfaction. Multicomponent interventions and positive leadership support proved most effective, while the use of technology such as online workshops also showed promise. However, there is still a need for longitudinal research and adaptation of interventions to local contexts. The results of this review are expected to provide theoretical and practical contributions in the development of positive psychology-based teacher welfare improvement programs.